The Effect Of Retained Earnings On Trading Volume Activity (TVA) With Return On Assets As A Moderation Variable - Prima Sari, Pristin; Prima Putra, Ardian; Rinofah, Risal (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
Trading Volume Activity (TVA) indicates the amount of stock trading volume in a company's stock market. Companies with good stock volume and financial performance can increase stock trading volume. The research aims to empirically examine the effect of retained earnings on Trading Volume Activity (TVA) with Return On Assets (ROA) as a moderating variable. The study uses data from the 2018-2020 financial statements of companies in the consumption and construction services sector listed on IDX and analyzed using moderation regression analysis. The results show that the variable retained earnings is simultaneously significant to Trading Volume Activity (TVA) with Return On Assets (ROA) as a moderating variable. Partially retained earnings can significantly influence Trading Volume Activity (TVA), while ROA can moderate the retained earnings variable on Trading Volume Activity (TVA). The research contributes that companies can increase the amount of retained earnings and increase ROA so that trading volume can be increased. The more companies trade, the value-added received will increase